Gross Motor Skills Training Leads to Increased Brain-Derived Neurotrophic Factor Levels in Healthy Older Adults: A Pilot Study - Grégoire, Catherine-Alexandra; Berryman, Nicolas; St-Onge, Florence; Vu, Thien Tuong Minh; Bosquet, Laurent; Arbour, Nathalie; Bherer, Louis (Frontiers in Physiology, 2019)
Exercise is recognized as a promising approach to counteract aging-associated declines in cognitive functions. However, the exact molecular pathways involved remain unclear. Aerobic training interventions and improvements in peak oxygen uptake (VO2peak) have been associated with increases in the peripheral concentration of brain-derived neurotrophic factor (BDNF) and better cognitive performances. However, other training interventions such as resistance training and gross motor skills programs were also linked with improvements in cognitive functions. Thus far, few studies have compared different types of physical exercise training protocols and their impact on BDNF concentrations, especially in participants over 60 years old. The main objective of this study was to compare the effects of three exercise protocols on plasma BDNF concentrations at rest in healthy older adults. Thirty-four older adults were randomized into three interventions: 1) lower body strength and aerobic training (LBS-A), 2) upper body strength and aerobic training (UBS-A), or 3) gross motor activities (GMA). All interventions were composed of 3 weekly sessions over a period of 8 weeks. Physical, biochemical, and cognitive assessments were performed pre and post-intervention. All interventions resulted in improved cognitive functions but the GMA intervention induced a larger increase in plasma BDNF concentrations than LBS-A. No correlation was observed between changes in BDNF concentrations and cognitive performances. These findings suggest that a program of gross motor activities could lead to enhancements in plasma BDNF concentrations. Moreover, cognition improvement could occur without concomitant detectable changes in BDNF, which highlights the multifactorial nature of the exercise-cognition relationship in older adults.